Integrative Islamic Values Model of Academic Supervision to Enhance Instructional Quality in Madrasah Ibtidaiyah: A Study in Barru Regency - Tajuddin, Tajuddin; Akib, Irwan; Mawardi, Amirah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to develop an Integrative Islamic Values Model of Academic Supervision designed to enhance instructional quality in Madrasah Ibtidaiyah (Islamic elementary schools) in Barru Regency, Indonesia. The research responds to the limited effectiveness of conventional supervision practices, which frequently emphasize administrative compliance rather than pedagogical improvement grounded in Islamic ethics. Employing a Research and Development (R&D) approach adapted from Borg and Gall, the study progressed through needs analysis, model design, expert validation, limited implementation, and wider field testing. Data were collected through interviews, observations, questionnaires, and documentation, and analyzed using descriptive statistics (mean and standard deviation) and qualitative techniques including thematic analysis. The findings indicate that the developed model incorporates core Islamic values—amanah (trust), ‘adl (justice), ihsan (excellence), musyawarah (consultation), and mas’uliyyah (responsibility)—into the planning, implementation, and evaluation stages of academic supervision. Expert assessments showed strong validity (M = 4.63/5.00), while field testing demonstrated significant improvements in teachers’ pedagogical competence and instructional quality, supported by increased mean scores across key performance indicators. This study contributes an empirically tested and contextually grounded framework that integrates Islamic spiritual values with professional supervision standards, offering a novel and practical model to strengthen holistic and ethically rooted instructional quality assurance in Madrasah Ibtidaiyah.